1983
DOI: 10.1111/j.1365-2230.1983.tb01815.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis herpetiformis: a review of 119 cases

Abstract: Relatively little is known about the occurrence of neurocysticercosis in northeastern Brazil. There have been no published reports from the state of Ceará, but a review of the records at the Hospital São José in Fortaleza, Brazil identified 119 patients with neurocysticercosis diagnosed between January 1988 and April 1994. Patients came from 43 municipalities in Ceará. Their ages ranged from five to 74 years; the greatest number of cases were in persons 10-40 years of age; 63% were males. Seizures were the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
3

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 27 publications
4
19
0
3
Order By: Relevance
“…DH is somewhat more common in men than in women with the ratio of 1.5 : 1 that is observed corresponding to the literature. The average age of somewhat over 40 years observed here also corresponds to the results of various large studies in other European nations and the USA [10–12].…”
Section: Discussionsupporting
confidence: 88%
“…DH is somewhat more common in men than in women with the ratio of 1.5 : 1 that is observed corresponding to the literature. The average age of somewhat over 40 years observed here also corresponds to the results of various large studies in other European nations and the USA [10–12].…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, rare cases of DH, developing in patients with GSE despite a strict GFD, have been reported in the literature. [14][15][16] In our patient, at the time of GSE diagnosis, anti-tTG antibodies were found to be elevated and disappeared completely after 6 months of a GFD. When the patient was given a diagnosis of DH 18 months later, only anti-eTG but not anti-tTG antibodies were found.…”
Section: Discussionmentioning
confidence: 85%
“…In an earlier study (33) we found nevus depigmentosis to be significantly associated with AD in children. Other associations are gluten-sensitive enteropathy (34), adult coeliac disease ( 3 9 , and dermatitis herpetiformis (36,37). Migraine has also been occasionally found to be associated with AD (1 1,12).…”
Section: Discussionmentioning
confidence: 99%